Prenatal Diagnosis of Concurrent Achondroplasia and Klinefelter Syndrome - Esther Perez-Carbajo; Ignacio Zapardiel; Luis Sanfrutos-Llorente; Sara Cruz-Melguizo; Cristina Martinez-Payo; Enrique Iglesias-Goy (Case Reports in Obstetrics and Gynecology)
Achondroplasia is the most frequent nonlethal skeletal dysplasia, with a prevalence of 1 : 5000 to 1 : 40,000 live births, and it is caused by a fibroblast growth factor receptor alteration. The combination of achondroplasia and Klinefelter syndrome is extremely rare and just four reports have been published in the literature, which were all diagnosed postnatally. We report the fifth case described of this uncommon association and its prenatal diagnosis. In cases of prenatal diagnosis of achondroplasia with additional suspicious morphological abnormalities, an invasive test such as amniocentesis must be carried out to assess the karyotype normality.